Qualitative Differences between Research Training and Education Research in Undergraduate Students - Barrios González, Erika Egleontina (2019)
Traditionally, training in research at the universities has been transmitted as theory (research training, RT); however, the nature of this knowledge benefits from a more practical approach (formative research, FR). The aim of this research was to compare the qualitative differences between these two types of approach to training in the research process. Four focus groups were created: 2 RT and 2 FR. Sixteen categories corresponding to the quantitative research process were chosen for the script, and a total of 30 Psychology students participated. Significant conceptual differences were found regarding the research process. FR students tend to have more clarity regarding concepts, take a larger number of ethical aspects into consideration, and develop an identity as researchers. They prefer qualitative research because of the difficulties they have with statistics. There is a linear view of the research process in both, and change-generating dynamism is perceived as a problem. In sum, the FR students acquire an overview of the process that is perfected with experience, in addition to contributing to an ethical vision and acquiring an identity as researchers, which shows advantages over the other type of training.